Manfaat Puasa dalam Perspektif Sunnah - Rindi Apriani; Aulia Putri Zahra; Andriyani Andriyani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Fasting is one of the main acts of worship in Islam that has profound meaning, both spiritualy, socially, and health-wise. This study aims to examine the benefits of fasting in the perspective of sunnah through a pure qualitative approach using the phenomenological method. The focus of the study is on how the practice of sunnah fasting, such as Monday-Thursday, Daud. Arafah, Ashura and Ayyamul Bidh, affects the increase in spiritually, inner peace, and sincerity of individuals. This study uses a qualitative approach with a library research method thar aims to examine the benefits of fasting in the perspesctive of sunnah. Data were obtained from various relevant literature sources, imcluding the Qur’an, hadith, fiqh books, and national jurnals listed in thebibliography with a publication range 2009-2024. The results of the study show that fasting not only serves as a form of obedience to Allah SWT, but also as a means of purifying the soul, controlling desires, and increasing social empathy. In addition, fasting has physiological benefits that can improve physical health. Thus, fasting in the perspective of sunnah is a comprehensive spiritual education shaping Muslims to be pious, patient and noble in character.